NOD mouse dorsal root ganglia display morphological and gene expression defects before and during autoimmune diabetes development - Corral-Pujol, Marta; Arpa, Berta; Rosell-Mases, Estela; Egia-Mendikute, Leire; Mora, Conchi; Stratmann, Thomas; Sanchez, Alex; Casanovas, Anna; Esquerda, Josep Enric; Mauricio, Didac; Vives-Pi, Marta; Verdaguer, Joan (Frontiers in Endocrinology, 2023)
Introduction: During the development of Autoimmune Diabetes (AD) an autoimmune attack against the Peripheral Nervous System occurs. To gain insight into this topic, analyses of Dorsal Root Ganglia (DRG) from Non-Obese Diabetic (NOD) mice were carried out. Methods: Histopathological analysis by electron and optical microscopy in DRG samples, and mRNA expression analyzes by the microarray technique in DRG and blood leukocyte samples from NOD and C57BL/6 mice were performed. Results: The results showed the formation of cytoplasmic vacuoles in DRG cells early in life that could be related to a neurodegenerative process. In view of these results, mRNA expression analyses were conducted to determine the cause and/or the molecules involved in this suspected disorder. The results showed that DRG cells from NOD mice have alterations in the transcription of a wide range of genes, which explain the previously observed alterations. In addition, differences in the transcription genes in white blood cells were also detected. Discussion: Taken together, these results indicate that functional defects are not only seen in beta cells but also in DRG in NOD mice. These results also indicate that these defects are not a consequence of the autoimmune process that takes place in NOD mice and suggest that they may be involved as triggers for its development.